REVITALIZING TRADITION: THE ROLE OF PAKAT PERKARA IN RESOLVING LAND DISPUTES WITHIN THE DAYAK TOBAG COMMUNITY - Seko, Salfius; Soa, Alfonsus Hendri (Faculty of Law, Universitas Diponegoro, 2025)
Land disputes are a significant issue, especially for Indigenous communities, where traditional customs play a central role in resolving conflicts. In Tebang Benua Village, Tayan Hilir District, Sanggau Regency, the Dayak Tobag community utilizes a unique dispute resolution mechanism known as Pakat Perkara, which focuses on negotiation and consensus-building to resolve land disputes. This study examines the effectiveness of the Pakat Perkara mechanism, which integrates local wisdom and customary law to foster harmony and social cohesion. While the mechanism promotes fairness and inclusivity, challenges arise in reaching agreements, especially when there are significant differences in interests. This research highlights the need for further development and strengthening of this approach to ensure it functions effectively in addressing disputes. It also emphasizes the importance of integrating customary law into the formal legal system, creating a more responsive and equitable framework for resolving land disputes. The study concludes by recommending the revitalization of customary courts and legal procedures to enhance Indigenous peoples' autonomy and justice, promoting sustainable land management and community empowerment.